DC motor educational kit: a teaching aid in control theory - Moreira, António Paulo G. M. (2017)
This paper describes a laboratory control theory experiment supported by the use of a DC Motor Educational Kit. The impact, as a teaching aid, of the proposed laboratory control experiment is evaluated, having in mind the student's feedback. The DC motor that is used in the developed educational Kit is the EMG30, being a low cost 12 Volt motor equipped with encoders and a 30:1 reduction gearbox. The experiment is based on real hardware and on simulation, using the SimTwo realistic simulation software. In order to implement the realistic simulation the EMG30 model was obtained. Students' feedback was acquired using a questionnaire and the results confirmed the importance given to these practical experiments.